Analyses and modeling of urban land use and road network interactions using spatial-based disaggregate accessibility to land use - Farhad Ahmadzai (Journal of Urban Management, 2020)
Rapid urbanization in developing countries enforces authorities to assess the sustainability and balanced development of urban cities from multiple perspectives and recommend appropriate solutions for policy and decision-makers. This study proposes spatial-based disaggregate accessibility to land use to figure out the influencing factors and key indicators that enable a comprehensive categorization of cities' subdivisions from the perspectives of urban land use and road transport network. A general GIS and statistical software programs-based methodology is adopted and validated in the case example of Kandahar City, located in Afghanistan. The methodology involves five major steps; 1) limited primary and secondary data collection regarding road network and land uses, 2) calculation of urban land uses weights, 3) identifying critical centers of neighborhood land uses, 4) estimation of origin-destination cost matrix, and; 4) formulating and modeling accessibility measures. The statistical and theoretical significances have been illustrated in the result. The final accessibility measures have divided the subdivisions of Kandahar City (case study) into three different categories, namely, a) high-level municipal districts (CBD), b) medium-level municipal districts (semi-urban), and; c) peripheral municipal districts. The research has incorporated qualitative and quantitative approaches for sustainable and balanced urban development.
Keywords: 710; Accessibility; Interactions; Land use; Municipal district; Road transport network; Subdivision